Preoperative Endoscopic Activity Predicts the Occurrence of Pouchitis After Ileal Pouch–Anal Anastomosis in Ulcerative Colitis: A Multicenter Retrospective Study in China - Xu, Weimin; Tang, Wenbo; Ding, Wenjun; Hu, Hang; Chen, Wenhao; Qian, Qun; Cui, Long; Ding, Zhao; Du, Peng (Frontiers in Surgery, 2021)
Pouchitis is the most common long-term complication after ileal pouch–anal anastomosis (IPAA) in ulcerative colitis (UC) patients. Ulcerative colitis endoscopic index of severity (UCEIS) and Mayo endoscopic score (MES) are widely used indices to evaluate endoscopic activity. This study aimed to clarify the predictive value of preoperative endoscopic activity on the occurrence of pouchitis after IPAA. Methods: Data of UC patients who underwent IPAA from January 2008 to January 2020 were retrospectively collected. UCEIS and MES were based on the preoperative colonoscopy findings of two independent endoscopists. Results: A total of 102 patients with a median follow-up of 5 (interquartile range, 2–9) years were included in the study. Among them, 21.6% developed pouchitis. Compared with MES, UCEIS had a stronger correlation with pouchitis disease activity index. UCEIS ≥7 had the most significant receiver-operating characteristic (ROC) curve area of 0.747 with a sensitivity of 68.2% and specificity of 81.2% in predicting pouchitis, which outperformed MES of 3 with an ROC area of 0.679 with a sensitivity of 54.5% and specificity of 81.2%. Furthermore, we found that UCEIS ≥7 was an independent risk factor for post-IPAA pouchitis [odds ratio (OR), 8.860; 95% confidence interval (CI), 1.969–39.865, p < 0.001] with a higher risk than MES of 3 (OR, 5.200; 95% CI, 1.895–14.273; p = 0.001). Conclusion: UCEIS performed better in predicting pouchitis after IPAA than MES. Earlier and more frequent postoperative colonoscopic surveillance should be considered in patients with preoperative UCEIS ≥7 to detect the occurrence of pouchitis eariler.